ETV5 facilitates tumor progression in head‐neck squamous cell carcinoma - Yu, Shijin; Ma, Zongjun; Chen, Tao; Wang, Hong; Yao, Qin; Li, Jin; Cheng, Jie (Oral diseases, 2024)
Objective E26 transformation‐specific (ETS) factors have emerged as key mediators underlying human tumorigenesis. Here, we sought to characterize the expression pattern, biological roles, and clinical significance of ETS Variant Transcription Factor 5 (ETV5) in head neck squamous cell carcinoma (HNSCC). Subjects and Methods ETV5 expression pattern in HNSCC was determined by bioinformatics interrogations and immunohistochemical staining in primary samples. The associations between its abundance with clinicopathological parameters, and patient survival were evaluated. Colony formation, CCK‐8, flow cytometry, wound healing, and Transwell invasion assays, as well as xenograft models, were utilized to determine the phenotypic changes after ETV5 silencing in vitro and vivo. The potential binding of ETV5 in the Slug promoter was determined by ChIP‐qPCR. Results ETV5 was significantly overexpressed in HNSCC samples. Its overexpression is significantly associated with aggressiveness features and reduced survival. ETV5 knockdown significantly inhibited cell proliferation, migration, invasion, and induced apoptosis in vitro, and impaired tumor growth in vivo. Moreover, ETV5‐activated Slug transcription by binding its promoter region in HNSCC cells. Patients with ETV5highSlughigh had the worst survival across multiple HNSCC cohorts. Conclusions Our findings reveal that ETV5 serves as a novel prognostic biomarker and putative oncogene for HNSCC progression likely by activating Slug transcription.